Effect of mutual funds characteristics on their performance and trading strategy: A dynamic panel approach - Inderjit Kaur (Cogent Economics & Finance, 2018)
Investors search for criteria that are systematically related to performance of mutual funds so as to maximize their personal return. The present study is on effect of selected fund characteristics on performance of the mutual funds. The data on Indian equity mutual funds for the period 2004-2013 was utilized for the purpose. The dynamic panel data is estimated with the most efficient estimator system-Generalized Method of Moment (sys-GMM). The results show that past year's performance, flow to funds, and cash ratio explained the fund performance measured with conditional Carhart alpha. Thus, earlier documented non-persistence in the performance of mutual funds could be due to not considering the dynamic effect of lagged dependent variable. Further, we examined whether mutual fund characteristics systematically affect the näive beta strategies followed by mutual funds. The findings show that fund characteristics such size, expense ratio, portfolio turnover ratio, and age affect trading strategy of mutual funds. The study has implications for investors of mutual funds as they can optimize their portfolio return with a strategy based on past one-year risk adjusted conditional Carhart alpha. Further, mutual fund ranking firms can consider conditional Carhart alpha as one of the criteria to rank mutual funds.
Keywords: 330; Mutual funds; fund characteristics; performance; dynamic panel; trading strategy; India